Pengaruh Literasi Keuangan dan Uang Saku Terhadap Pengelolaan Keuangan Mahasiswa S1 Prodi Manajemen Angkatan Tahun 2018 Fakultas Ekonomi dan Bisnis (Studi pada Mahasiswa Universitas Islam Malang) - Safitri Safitri; Ronny Malavia Mardani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to analyze finances, and determine the effect of literacy andpocket money on the financial management of S1 Management students of the faculty of Economics and Business class of 2018 Islamic Universitas of Malang. This type of research uses explanatory research using a quantitave approach and data collection techniques used in this study are data use statistics as an analysis technique. In this study, the sample used is 106 students who will be the object of research. This sampling technique uses a probability sampling method in a proportional stratified random sampling. Where the results of this study indicate that financial literacy has a significant positive effect on student financial management, and pocket money also shows that pocket money has a significant positive effect on student financial management. Keywords: financial literacy, pocket money and student finance